Wanita dengan Sindrom Rupus : Lupus Eritematosus Sistemik dan Artritis Reumatoid - Amiruddin, Asriani (Alami Journal (Alauddin Islamic Medical) Journal, 2017)
Background : The coexistence of two or more connective tissue diseases in the same patient is a rare phenomenon, particularly the coexistence of Sytemic Lupus Erythematosus (SLE) and Rheumatoid Arthrtitis (RA) (0,01 to 2%). Rhupus syndrome is a symmetric deforming polyarthritis of the small and large joints which is erosive on radiography and accompanied by clinical signs and symptoms of SLE and by the presence of specific autoantibodies with high specificity. Case : A young female, 29 years old with symmetric polyarthritis of both upper and lower limb joints for last six months and was developed in two weeks. There was a history of hair loss for least 1 year. She also gave history of recurrent painful oral ulcers for last 6 months. Examination revealed alopecia, pallor, malar rash, and symmetric polyarthritis. The laboratory results were anemia, thrombocytopenia, positive anti-cyclic citrullinated peptide antibodies, positive rheumatoid factor, increased erythrocyte sedimentation rate, and the immunologic disorder characterized by positive anti-Sm. Plain radiographs of both hands showed erosive polyarthritis. The treatment with methyl prednisolone, methotrexate, calcium, and folic acid. During treatment, she achieved clinical remission. Discussion : Symmetric polyarthritis at the young age are affected in 90% of the patients with SLE and RA. The beginning of which could not be defined, was coexistent with this overlap syndrome. Diagnosis of RA based on American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) and diagnosis of SLE based on ACR 1997 criteria. The therapy include low to moderate doses systemic corticosteroid and combination with 1-3 Disease-modifying anti-rheumatic drugs (DMARDs).